The function and mechanisms of action of circular RNAs in Urologic Cancer - Zhang, Zi-hao; Wang, Yue; Zhang, Ya; Zheng, Sheng-Feng; Feng, Tao; Tian, Xi; Abudurexiti, Mierxiati; Wang, Zhen-Da; Zhu, Wen-Kai; Su, Jia-Qi; Zhang, Hai-Liang; Shi, Guo-Hai; et al. (Molecular cancer, 2023)
Kidney, bladder, and prostate cancer are the three major tumor types of the urologic system that seriously threaten human health. Circular RNAs (CircRNAs), special non-coding RNAs with a stabile structure and a unique back-splicing loop-forming ability, have received recent scientific attention. CircRNAs are widely distributed within the body, with important biologic functions such as sponges for microRNAs, as RNA binding proteins, and as templates for regulation of transcription and protein translation. The abnormal expression of circRNAs in vivo is significantly associated with the development of urologic tumors. CircRNAs have now emerged as potential biomarkers for the diagnosis and prognosis of urologic tumors, as well as targets for the development of new therapies. Although we have gained a better understanding of circRNA, there are still many questions to be answered. In this review, we summarize the properties of circRNAs and detail their function, focusing on the effects of circRNA on proliferation, metastasis, apoptosis, metabolism, and drug resistance in kidney, bladder, and prostate cancers.